Bedtime versus morning use of antihypertensives for cardiovascular risk reduction (BedMed): protocol for a prospective, randomised, open-label, blinded end-point pragmatic trial. Issue 2 (24th February 2022) - Garrison, Scott R; Kolber, Michael R; Allan, G Michael; Bakal, Jeffrey; Green, Lee; Singer, Alexander; Trueman, Darryl R; McAlister, Finlay A; Padwal, Raj S; Hill, Michael D; Manns, Braden; McGrail, Kimberlyn; et al.
Abstract : Introduction: Sleep-time blood pressure correlates more strongly with adverse cardiovascular events than does daytime blood pressure. The BedMed trial evaluates whether bedtime antihypertensive administration, as compared with conventional morning use, reduces major adverse cardiovascular events. Methods and analysis: Design Prospective randomised, open-label, blinded end-point trial. Participants Hypertensive primary care patients using blood pressure lowering medication and free from glaucoma. Setting Community primary care providers in 5 Canadian provinces (British Columbia, Alberta, Saskatchewan, Manitoba and Ontario) are mailing invitations to their eligible patients. Social media campaigns (Google, Facebook) are additionally running in the same provinces. Intervention Consenting participants are allocated via central randomisation to bedtime vs morning use of all antihypertensives. Follow-up (1) Telephone or email questionnaire at 1 week, 6 weeks, 6 months and every 6 months thereafter, and (2) accessing linked governmental healthcare databases tracking hospital and community medical services. Primary outcome Composite of all-cause death, or hospitalisation for myocardial infarction/acute-coronary syndrome, stroke or congestive heart failure. Secondary outcomes Each primary outcome element on its own, all-cause hospitalisation or emergency department visit, long-term care admission, non-vertebral fracture, new glaucoma diagnosis, 18-month cognitive decline from baseline (via Short Blessed Test). Select other outcomes Self-reported nocturia burden at 6 weeks and 6 months (no, minor or major burden), 1-year self-reported overall health score (EQ-5D-5L), self-reported falls, total cost of care (acute and community over study duration) and mean sleep-time systolic blood pressure after 6 months (via 24-hour monitor in a subset of 302 sequential participants). Primary outcome analysis Cox proportional hazards survival analysis. Sample size The trial will continue until a projected 254 primary outcome events have occurred. Current status Enrolment ongoing (3227 randomised to date). Ethics and dissemination: BedMed has ethics approval from six research ethics review boards and will publish results in a peer-reviewed journal. Trial registration number: NCT02990663 .